Using commercial marketing approach to deliver health and prevention: helping to promote self-care - Elham Shakibazadeh (Tehran University of Medical Sciences, 2014)
Self-care is a series of learned actions and goal-directed activities done by individuals in order to provide, maintain, and promote health. Self-care activities involve health promotion, disease prevention, treatment of diseases and injuries, and treatment of chronic diseases. Although the impact of the self-care on improvement of health outcomes and reduction of costs are proven in numerous studies, implementation of self-care programs requires systematic educational and supportive interventions provided by health care providers including nurses to overcome health problems. Many health professionals in Iran emphasize on negative aspects of unhealthy behaviors to persuade people to do preventive and healthy behaviors. For example, in drug abuse preventive programs, disadvantages of drug abuse as well as the increasing rate of drug abuse and other addictive behaviors, and the economic costs resulting from drug abuse are presented to youth. Although the emphasis on negative aspects and side effects of unhealthy behaviors is worthy, especially when negotiating the budget with the competent organizations and key supplier, it is not always the best way of proposing behavior change to individuals. For example, showing the pictures of amputated parts of body, and/or blindness to patients with diabetes who are mostly depressed and seek treatment in the diabetes clinics does not seem to be an appropriate approach. Is not there any other positive ways to announce messages to people? To answer this question, letchr('39')s take a look at the concept of commercial marketing. Do successful companies highlight negative content of their products and services? The answer is: not often. In commercial marketing, products are presented in a positive way. In fact, everything from cars to clothing, from food products to furniture is offered positively in the market. Car reminds success, health and welfare; cloths helps people to seem younger and more fit; food products help people to feel refreshed, healthy and happy; even furniture is for a modern and convenient life. In commercial marketing, foot blisters of a walking individual are never shown to make people to buy cars.